Biopsychosocial factors and falls among older adults during the COVID-19 pandemic: a longitudinal study - Renata Zacharias Grando; Letícia Pophal Cutisque; Alyssa Cristine de Oliveira Elias; André Luiz Felix Rodacki; Natália Boneti Moreira (Revista Brasileira de Atividade Física e Saúde)
The restrictions imposed by the COVID-19 pandemic impacted the older adult population. Therefore, this study aimed to investigate the difference between timeline changes (baseline vs. final assessment) of the biopsychosocial factors and fall prevalence during the pandemic; the differences between infected and non infected older adults regarding the biopsychosocial approach; and to describe the characteristics of post-COVID falls. Thirty-one community-dwelling older adults (70.9 ± 5.6 years,♀20) were evaluated twice in one year. The variables tested were based on the biopsychosocial approach: diseases and COVID-19 infection (Health Conditions), body mass index, cognition, and depression (Body Functions and Structures), physical activity, sedentary behavior (SB), and functional capacity (Activity), health-related quality of life (HRQoL, Participation), medications (Environmental), falls history and fear of falling (Personal). Cohen’s effect size (d) was used in data analysis. Comparing the timeline changes (baseline vs. final assessment) the biopsychosocial factors were worst in Activities (SB, d = 0.70) and Personal Factors (Fear of falling, d = 4.06). The infected older adults showed worst scores in Body Functions and Structures (Cognition, d = 0.77), Activity (SB, d = 0.55), Participation (HRQoL domains, d = from 0.31 to 0.78), and Personal Factors (Fear of falling, d = 0.54). Falls prevalence enhanced between the evaluations (12.9%) and was higher in infected older adults compared to not infected (63.6% vs. 25%). Older adults showed negative changes during the pandemic in most biopsychosocial domains, especially in older adults with COVID infection and in aspects related to falls, SB, and HRQoL compared to their counterparts without COVID infection.